Dynamic Control of Sacrificial Bond Transformation in the Fe−N−C Single‐Atom Catalyst for Molecular Oxygen Reduction. Issue 48 (21st October 2021) - Yu, Li; Li, Yuchan; Ruan, Yuefei
Abstract: Atomically dispersed metal‐nitrogen sites show great prospect for the oxygen reduction reaction (ORR), whereas the unsatisfactory adsorption‐desorption behaviors of oxygenated intermediates on the metal centers impede improvement of the ORR performance. We propose a new conceptual strategy of introducing sacrificial bonds to remold the local coordination of Fe−N x sites, via controlling the dynamic transformation of the Fe−S bonds in the Fe−N−C single‐atom catalyst. Spectroscopic and theoretical results reveal that the selective cleavage of the sacrificial Fe−S bonds induces the incorporation of the electron‐withdrawing oxidized sulfur on the Fe centers. The newly functionalized moieties endow the catalyst with superior ORR activity and remarkable stability, owing to the reduced electron localization around the Fe centers facilitating the desorption of ORR intermediates. These findings provide a unique perspective for precisely controlling the coordination structure of single‐atom materials to optimize their activity. Abstract : Bond breaking/re‐formation to tune local coordination: Deliberate construction and subsequent selective cleavage of sacrificial Fe−S bonds render flexible tunability to control the local coordination of metal single atoms. The oxidized sulfur functionalization around the Fe center helps the Fe−N−C reach the ORR volcano‐plot apex by optimizing the adsorption strength of the oxygenated intermediates.